2014
DOI: 10.1139/gen-2013-0188
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cysteine protease-like genes in the striped rice stem borer, Chilo suppressalis

Abstract: The striped rice stem borer, Chilo suppressalis (Walker), is a major pest for rice production in China and the rest of Southeast Asia. Chemical control is the main means to alleviate losses due to this pest, which causes serious environmental pollution. An effective and environmentally friendly approach is needed for the management of the striped rice stem borer. Cysteine proteases in insects could be useful targets for pest management either through engineering plant protease inhibitors, targeting insect dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Although only one DEG (c60073_g1) belonging to cysteine protease family was identified in our study, it was significantly up-regulated in C. suppressalis larvae feeding on water-oat in comparison with those feeding on rice. This result is consistent with the previous study 48 . Another DEG (c53074_g1) in the digestive gene list was found to be the same as the serine protease inhibitor gene CS003 , which had been identified in C. suppressalis midgut 49 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although only one DEG (c60073_g1) belonging to cysteine protease family was identified in our study, it was significantly up-regulated in C. suppressalis larvae feeding on water-oat in comparison with those feeding on rice. This result is consistent with the previous study 48 . Another DEG (c53074_g1) in the digestive gene list was found to be the same as the serine protease inhibitor gene CS003 , which had been identified in C. suppressalis midgut 49 .…”
Section: Discussionsupporting
confidence: 94%
“…Ge et al . reported previously that the expression of three digestive cysteine protease genes in C. suppressalis was significantly affected by the host plant type 48 . Although only one DEG (c60073_g1) belonging to cysteine protease family was identified in our study, it was significantly up-regulated in C. suppressalis larvae feeding on water-oat in comparison with those feeding on rice.…”
Section: Discussionmentioning
confidence: 87%
“…The striped stem borer Chilo suppressalis Walker (Lepidoptera: Pyralidae) is a widespread rice pest that poses a major threat to food security throughout Asia, including China, India, Sri Lanka, Japan and Malaysia [1][2][3]. Excessive application of chemical pesticides has led to the rapid evolution of insect resistance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various functional studies suggest the involvement of cathespins other than CathL in molting and metamorphosis (Liu et al, 2006). Midgut specific CathF and hemolymph specific CathO are found in Chilo suppressalis and B. mori along with CathL (Ge et al, 2014;Zhang et al, 2015). Additionally, CathB is observed in the granulocytes and plasmatocytes of H. armigera larvae specifically at the prepupation stage (sixth instar), implicating its role in larva to pupa transition (Yang et al, 2007).…”
Section: Indispensability and Functionality Of Cathepsins In Insect Dmentioning
confidence: 99%
“…Elevated temperature and oxidative stress led to the overexpression of CathB and D, which results in shorter larval life span of B. mori and early pupation (Kim et al, 2011;Wu et al, 2011). Recently, Ge et al (2014) explored the effect of starvation on cathepsins from C. suppressalis and found that CathB, O and L were upregulated in response to food deprivation. Although the studies relating to the role of cathepsins in stress response are in infancy, these studies give a hint that different cathepsins play a role in response to diverse stress conditions in lepidopteran insects.…”
Section: Cathepsins In Insect Biotic and Abiotic Stress Responsementioning
confidence: 99%